A director’s journey on a road trip : take me home - Ho, Kylen Jia En (Nanyang Technological University, 2021)
This report analyses the thought process, inspiration and motifs behind the film, Take Me Home. It includes references and an extensive reflection of a year's work through the eyes of a director on a road trip film.